Auditor's Loss Functions Implicit in Consumption-Investment Model - Scott, William R. (Journal of Accounting Research, 1975)
In a previous paper,' I demonstrated how the problems faced by the auditor of a firm's published annual financial statements in deciding (1) how much audit evidence to obtain and (2) what set of balance sheet valuation numbers to choose in the light of this audit evidence can be regarded as a problem in Bayesian point estimation. In effect, the auditor was viewed as picking a vector of numbers (the balance sheet) to summarize his posterior probability distribution (i.e., posterior to his audit examination) of those balance sheet parameters for which he is held responsible by the nature of his audit engagement. He does this subject to a loss function whereby he is penalized for discrepancies between the balance sheet numbers so chosen and their subsequent realization. Given the professional nature of the auditor's engagement, it seems reasonable to suggest that this loss function really derives from the various financial statement users. If they rely on the audited statements as inputs into decisions when those statements contain auditor's errors, they will suffer an opportunity loss of expected utility. This raises the question, of course, of who these users are and how financial statement errors operate to cause utility losses. The approach in this paper is to pick a specific, well-defined normative decision problem for which audited financial statements have the potential to be useful and find the loss function that is implicit in it. The problem I have chosen is an individual's consumption-investment